"Stiff–Soft" Binary Synergistic Aerogels with Superflexibility and High Thermal Insulation Performance. (14th February 2019) - Zhang, Junyan; Cheng, Yanhua; Tebyetekerwa, Mike; Meng, Si; Zhu, Meifang; Lu, Yunfeng
Abstract: Designing aerogel materials featuring both high thermal insulation property and excellent mechanical robustness is of great interest for applications in superior integrated energy management systems. To meet the above requirements, composite aerogels based on hierarchical "stiff–soft" binary networks are reported, in which secondary mesoporous polymethylsilsesquioxane domains intertwined by bacterial cellulose nanofibrillar networks are connected in tandem. The resulting composite aerogels are characterized by highly porous (93.6%) and nanosized structure with a surface area of 660 m 2 g −1, leading to the excellent thermal insulation performance with a low thermal conductivity of 15.3 mW m −1 K −1 . The integrated "stiff–soft" binary nature also endows the composite aerogels with high flexibility that can conform to various substrates as well as large tensile strength that can withstand more than 2.70 × 10 4 times its own weight. These composite aerogels show multifunctionality in terms of efficient wearable protection, controllable thermal management, and ultrafast oil/water separation. These favorable multifeatures present composite aerogels ideal for aerospace, industrial, and commercial applications. Abstract : Hierarchical "stiff–soft" binary composite aerogels with superflexibility and high thermal insulation performance are developed, in which secondary mesoporous polymethylsilsesquioxane domains intertwined by bacterial cellulose nanofibrillar networks are connected in tandem. The resulting composite aerogels are highly porous, strong, superflexible, and hydrophobic, showing multifunctionality in terms of efficient wearable protection, controllable thermal management, and ultrafast oil/water separation.